Water-Bath Calibration Device with Data Storage Using Six Thermocouple Sensor - Kusumawardani, Yanti; Dian Setioningsih, Endang; Titisari, Dyah (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Uneven temperature distribution in the water-bath chamber can cause the temperature conditions in the chamber are not the same. Temperature, humidity, atmospheric pressure, and dust particles are the main factors that adversely affect the accuracy of the water bath’s temperature. Therefore, the purpose of this study is to design a calibration device for water-bath with six-channel temperature sensors. In this study, the system able to detect temperatures at each point. The K-type thermocouple sensor is used to detect the temperature at each chamber point with the help of the MAX6675 module as a signal conditioning amplifier. The sensor readings will be displayed on a personal computer using a USB cable, and the sensor readings can be stored on a personal computer in the TXT format so that the data can be reprocessed using Microsoft Excel for further calibration purposes. This study aims to facilitate the calibration process and the processing of calibration data. Based on the obtained measurements, a temperature error for 40 ° C channel one 1.4 %, channel two 1.8%, channel three 0.4%, channel four 0.2%, channel five 0.2% and channel 6 0.2%. Furthermore, the accuracy for temperature setting of 50 ° C for channel one 2.25%, channel two 2.26%, channel three 2.00%, channel four 2.44%, channel five 2% and channel six 1.6%. Moreover, the accuracy for setting temperature 60 ° C for channel one is 0.3%, channel two 0.6%, channel three 0.5%, channel four 1.5%, channel five 2% and channel six 1.8%. Based on the test results, this design has the lowest error of 0.2% and the highest error of 2.44%. The results of this research can be implemented as a water bath calibrator device to maintain the temperature stability of the instrument.